The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/plants11192632
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Quorum-Sensing Potential of Ethanolic Extracts of Aromatic Plants from the Flora of Cyprus

Abstract: Quorum sensing (QS) is a form of intra- and inter-species communication system employed by bacteria to regulate their collective behavior in a cell population-dependent manner. QS has been implicated in the virulence of several pathogenic bacteria. This work aimed to investigate the anti-QS potential of ethanolic extracts of eight aromatic plants of Cyprus, namely, Origanum vulgare subsp. hirtum, Rosmarinus officinalis, Salvia officinalis, Lavendula spp., Calendula officinalis, Melissa officinalis, Sideritis c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…In this study, we investigated the effects of V. adoensis root extract on P. aeruginosa swimming and swarming motilities and found that the extract had no effect on the motility of the bacterium. However, there are studies which have shown that plant extracts can inhibit the motility of P. aeruginosa [ 65 ]. Antibiofilm agents may influence biofilm formation by damaging microbial membrane structures, inhibiting peptidoglycan synthesis and/or modulating quorum sensing [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated the effects of V. adoensis root extract on P. aeruginosa swimming and swarming motilities and found that the extract had no effect on the motility of the bacterium. However, there are studies which have shown that plant extracts can inhibit the motility of P. aeruginosa [ 65 ]. Antibiofilm agents may influence biofilm formation by damaging microbial membrane structures, inhibiting peptidoglycan synthesis and/or modulating quorum sensing [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The steps for detecting the activity of culture supernatant can refer to reference and be modified as appropriate ( Panayi et al, 2022 ). The steps are as follows: Vibrio harveyi ( V. harveyi ) BB170 is inoculated in autoinducer bioassay (AB) culture medium and cultured overnight at 30°C.…”
Section: Methodsmentioning
confidence: 99%
“…The steps for detecting the activity of culture supernatant can refer to reference and be modified as appropriate (Panayi et al, 2022). The steps are as follows: Vibrio harveyi (V. harveyi) BB170 is inoculated in autoinducer bioassay (AB) culture medium and cultured overnight at 30 • C. Before detection, the overnight culture solution of V. harveyi BB170 was diluted with fresh AB medium at a ratio of 1:5,000, and shaken well.…”
Section: Ai-2 Binding Assays In Vitromentioning
confidence: 99%
“…As shown in Table-2 [49,[52][53][54][55][56][57][58], a Delftia tsuruhatensis extract inhibited biofilm, motility, elastase activity, and protease activity in P. aeruginosa. The extract suppressed the expression of the quorum sensing genes LasI, LasR, RhlI, and RhlR.…”
Section: P Aeruginosamentioning
confidence: 96%
“…Similarly, copper nanoparticles synthesized using Cardiospermum halicacabum leaf extract inhibited the development of P. aeruginosa biofilms [61]. The nanoparticles could attach to the bacterial cells, disrupting the bacterial cell wall or cell membrane to inhibit biofilm formation [58,61].…”
Section: Bacterial Clearancementioning
confidence: 99%